(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The automotive industry is among the prominent industry contributing to the Malaysian GDP rose by 3.6%, with a value of RM 40 billion in 2016. The automotive industry is one of the fastest-growing economic sectors in all other sectors with the primary purpose of providing safe and accessible transportation for the world’s increasing population. The vehicle owner and demand increase, but in the same way, road traffic accidents reported higher each year even though ASEAN NCAP has been introduced to improve the car safety level. Thus, this study aims to investigate further the technology shift and design features as external and internal environmental scanning towards car safety design and manufacturing from car manufacturer perspectives